2011
DOI: 10.1186/1471-2105-12-317
|View full text |Cite
|
Sign up to set email alerts
|

NoD: a Nucleolar localization sequence detector for eukaryotic and viral proteins

Abstract: BackgroundNucleolar localization sequences (NoLSs) are short targeting sequences responsible for the localization of proteins to the nucleolus. Given the large number of proteins experimentally detected in the nucleolus and the central role of this subnuclear compartment in the cell, NoLSs are likely to be important regulatory elements controlling cellular traffic. Although many proteins have been reported to contain NoLSs, the systematic characterization of this group of targeting motifs has only recently bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 39 publications
(30 reference statements)
5
140
0
2
Order By: Relevance
“…No nucleolar distribution of SERBP1 was suggested by nucleolar proteomic analyzes of the dynamic distribution under virus infection [25,26] or DNA damage [27]. However, two nucleolar localization signals in the N-terminus were determined using NoD [28]. Another putative signal with a value slightly below the 0.8 threshold was present at the C-terminus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No nucleolar distribution of SERBP1 was suggested by nucleolar proteomic analyzes of the dynamic distribution under virus infection [25,26] or DNA damage [27]. However, two nucleolar localization signals in the N-terminus were determined using NoD [28]. Another putative signal with a value slightly below the 0.8 threshold was present at the C-terminus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells in a 35 mm dish grown to~50% confluence were transfected with plasmids using Lipofectamine 2000 (Invitrogen/Life Technologies, Grand Island, NY, [28] as being above the 0.8 threshold are highlighted in yellow. A putative signal slightly below the threshold is highlighted in green.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Prediction of nucleolar localization sequences (NoLS) (26,27) suggested that FGF13 1A contains such elements near its N terminus (Fig. S3C), a region absent in FGF13 isoforms reported to be cytoplasmic (15).…”
Section: Resultsmentioning
confidence: 99%
“…Several previously unknown NoLS have been experimentally confirmed thereafter. 18,27 However, a considerably false positive prediction rate especially among sequences from nuclear proteins raises the question of how NLS and NoLS can be distinguished. The difference in the composition of a standard NLS and the peptides that accumulate in nucleoli is rather subtle, with the NLS being a few basic charged amino acids shorter than, e.g., the nucleolar marker peptide of 10 arginines described by us.…”
Section: -11mentioning
confidence: 99%